(untitled) (Modern American Journal of Medical and Health Sciences, 2025)
Gastrointestinal diseases and biliary dysfunction are among the most prevalent chronic systemic disorders and are frequently associated with metabolic disturbances that affect multiple organs and tissues, including the oral cavity. In recent years, increasing scientific attention has been directed toward the relationship between gastrointestinal pathology and alterations in hard dental tissues, particularly enamel and dentin. These changes are primarily mediated by disturbances in mineral metabolism, acid–base balance, and salivary protective mechanisms.